2011
DOI: 10.1103/physrevb.84.220102
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic mapping of local structural distortions in ferroelectric PbTiO3/SrTiO3superlattices at the unit-cell scale

Abstract: The local structural distortions in polydomain ferroelectric PbTiO 3 /SrTiO 3 superlattices are investigated by means of high spatial and energy resolution electron-energy-loss spectroscopy combined with high-angle annular dark field imaging. Local structural variations across the interfaces have been identified with unit-cell resolution through the analysis of the energy-loss near-edge structure of the Ti L 2,3 and O K edges. Ab initio and multiplet calculations of the Ti L 2,3 edges provide unambiguous evide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 33 publications
7
41
0
Order By: Relevance
“…The largest shift of this peak occurs on approaching the grain boundary, leading to a spectrum shape which has a remarkable resemblance to the O-K edge of bulk PTO. 31 This shift confirms how the bonding nature of oxygen is altered as a function of the change in the A-site chemistry between the more BTO-like bulk-of-grain regions compared to the Pb-rich grain boundary regions. To rule out any orientation effects influencing the ELNES the same area was measured twice, once with the bottom grain tilted onto zone axis, and once with the top grain tilted onto zone axis, similar features were seen either side of the grain boundary (Fig.…”
Section: -6supporting
confidence: 64%
See 3 more Smart Citations
“…The largest shift of this peak occurs on approaching the grain boundary, leading to a spectrum shape which has a remarkable resemblance to the O-K edge of bulk PTO. 31 This shift confirms how the bonding nature of oxygen is altered as a function of the change in the A-site chemistry between the more BTO-like bulk-of-grain regions compared to the Pb-rich grain boundary regions. To rule out any orientation effects influencing the ELNES the same area was measured twice, once with the bottom grain tilted onto zone axis, and once with the top grain tilted onto zone axis, similar features were seen either side of the grain boundary (Fig.…”
Section: -6supporting
confidence: 64%
“…30 The most striking feature observed here is a gradual shift in the peak marked with an asterisk. This peak is recognized to arise from the hybridization of the O-2p orbitals with states attributed to the A-site cation, 31 making it possible to distinguish a chemical transition in the A-site (Ba, Pb, and Ca). The largest shift of this peak occurs on approaching the grain boundary, leading to a spectrum shape which has a remarkable resemblance to the O-K edge of bulk PTO.…”
Section: -6mentioning
confidence: 99%
See 2 more Smart Citations
“…While the results of the superlattices asymmetrically sandwiched between Nb-doped SrTiO 3 (bottom) and gold (top) electrodes were consistent with a monodomain configuration, 28 those corresponding to the use of symmetrically coated SrRuO 3 electrodes (both top and bottom) suggested a polydomain phase with DW motion, which dynamics might be quite different than the conventional one. 29 Furthermore, through a combination of x-ray diffraction, transmission electron microscopy, and ultrahigh resolution electron energy loss spectroscopy (EELS), Zubko et al 30,31 have also recently showed the progressive transition between two different regimes, controlled by the thickness of the individual SrTiO 3 and PbTiO 3 layers. In the first regime, present for sufficiently thin paraelectric layers, SrTiO 3 and PbTiO 3 are strongly electrostatically coupled: a uniform monodomain polarization is adopted throughout the thickness of the superlattice to minimize the depolarizing field.…”
Section: Introductionmentioning
confidence: 99%